2016
DOI: 10.2147/ijn.s104851
|View full text |Cite
|
Sign up to set email alerts
|

Improving the osteogenesis of human bone marrow mesenchymal stem cell sheets by microRNA-21-loaded chitosan/hyaluronic acid nanoparticles via reverse transfection

Abstract: Cell sheet engineering has emerged as a novel approach to effectively deliver seeding cells for tissue regeneration, and developing human bone marrow mesenchymal stem cell (hBMMSC) sheets with high osteogenic ability is a constant requirement from clinics for faster and higher-quality bone formation. In this work, we fabricated biocompatible and safe chitosan (CS)/hyaluronic acid (HA) nanoparticles (NPs) to deliver microRNA-21 (miR-21), which has been proved to accelerate osteogenesis in hBMMSCs; then, the CS/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 35 publications
(57 reference statements)
1
12
0
Order By: Relevance
“…A number of miRNAs enhance the osteogenic differentiation of MSCs; hence, they have been pointed out as potential therapies to promote bone regeneration. For example, scaffolds and particles loaded with analogs of miR‐21 or miR‐148 potentiate bone regeneration in experimental models, at least in part, by interacting with the RUNX2 pathway . On the other hand, anti‐sense oligonucleotides and “sponges” inhibiting miR‐22, miR‐29, miR‐31, miR‐133, miR‐138, or miR‐214 have a stimulatory effect on osteogenesis and may improve fracture healing .…”
Section: Non‐coding Rnas In Skeletal Disordersmentioning
confidence: 99%
“…A number of miRNAs enhance the osteogenic differentiation of MSCs; hence, they have been pointed out as potential therapies to promote bone regeneration. For example, scaffolds and particles loaded with analogs of miR‐21 or miR‐148 potentiate bone regeneration in experimental models, at least in part, by interacting with the RUNX2 pathway . On the other hand, anti‐sense oligonucleotides and “sponges” inhibiting miR‐22, miR‐29, miR‐31, miR‐133, miR‐138, or miR‐214 have a stimulatory effect on osteogenesis and may improve fracture healing .…”
Section: Non‐coding Rnas In Skeletal Disordersmentioning
confidence: 99%
“…There are ongoing investigations to obtain the best results in bone regeneration with MSC sheets. Some of the biomaterials and/or biological agents reported to be combined with MSC sheets to enhance osteogenesis include coral particles [ 47 ], ceramics [ 48 ], surface-modified titanium and zirconia [ 82 ], simvastatin [ 83 ], β -tricalcium phosphate [ 84 ], coumarin-like derivative osthole [ 85 ], CD34+ peripheral blood cells [ 86 ], a complex of polyethylenimine-alginate nanocomposites plus BMP2 gene [ 87 ], nonviral oligonucleotide antimiR-138 delivery to MSC sheets [ 88 ], platelet-rich fibrin [ 89 , 90 ], vitamin C [ 91 ], poly(dimethylsiloxane) surface silanization [ 92 ], stromal cell-derived factor-1 [ 93 ], microRNA-21-loaded chitosan/hyaluronic acid nanoparticles [ 94 ], hydroxyapatite particles [ 90 , 95 ], and Notch activation by Jagged1 in MSC sheet cultures [ 96 ].…”
Section: The Use Of Msc Sheets In Combination With Scaffolds And/omentioning
confidence: 99%
“…used a microarc-oxidized titanium surface with miRNA-21loaded hyaluronic acid nanoparticles, and they confirmed that this scaffold promotes osteogenic differentiation on human bone marrow mesenchymal stem cells. [44][45][46] There are no clinical trials entries using miRNAs or antagomirs as bone diseases therapy in clinicaltrial.gov to date. However, there is study from Moscow State University started in 2017, that evaluates the safety and efficacy of a gene-activated bone substitute consisting of octacalcium phosphate and plasmid DNA encoding vascular endothelial growth factor for maxillofacial bone regeneration.…”
Section: Inhibit Bone Formation and Differentiationmentioning
confidence: 99%